Perbedaan Subtitusi Tepung Kacang Koro Pedang (Canavalia Ensiformis) pada Bakso Daging Analog Terhadap Kualitas Inderawi Kesukaan dan Kandungan Protein : Subtitusi Tepung Kacang Koro Pedang (Canavalia Ensiformis) pada Bakso Daging Analog - Kisworo, Firstia Artisantika; Saptariana; Bambang Sugeng Suryatna; Octavianti Paramita (LPPM Universitas Negeri Jakarta, 2024)
In this research, the use of jack beans will be used as an ingredient in making analog meatballs, in order to determine the sensory quality, preferences and protein content of analog meatballs. The aim of this research was to find out the differences in sensory quality, people's preferences and the nutritional content of protein contained in analog meatballs substituted for jack bean flour with percentages of 0%, 10%, 20% and 30%. The experimental design uses a single factor completely randomized design (CRD) experimental design. The data collection method for testing people's preferences uses 80 untrained panelists and is analyzed using the mean. The protein content test was carried out using the Kjeldahl method in the laboratory. The highest results in the sensory test showed a score of 4.1 in the texture aspect, 4.2 in the aroma aspect, 4.5 in the taste aspect, and 4.3 in the flavor aspect. The highest people's liking test results were in the texture aspect of 4.5 (liked), the aroma aspect was 4.03 (somewhat liked), the taste aspect was 4.13 (somewhat liked), and the color aspect was 4.08 (somewhat liked). The test results for the protein content of meat basko analog substitute for jack bean flour without treatment (100%:0%) were 17.46%, samples with 10% treatment produced 22.39%, with 20% treatment produced 25.36% and with 30% treatment resulted in 28.32%. Conclusions based on the test results of the preference for meatballs substituted with jack bean flour had the criteria of liking to somewhat liking, and the protein content increased along with the addition of the percentage of jack bean flour.